Stakeholders’ Awareness and Acceptability of the Leyte Normal University’s Vision, Mission, Goal and Objectives - Laurente, Mark Lester (International Journal for Innovation Education and Research, 2019)
This study determines the awareness of the stakeholders on the vision, mission, goals, and objectives (VMGO) and how these are disseminated; evaluates the stakeholders’ understanding and acceptance of the VMGO. It uses a descriptive type of research using the survey approach, with a stakeholder survey questionnaire to gather data. Results show that the stakeholders are generally aware, understand and accept the VMGO. The study also reveals that the stakeholders generally perceive that the VMGO are clearly stated, consistent with each other, congruent to educational practices or activities, and attainable. It also shows that the internal stakeholders, especially the administrators and faculty members, are much aware, understand and accept the VMGO than the external stakeholders. The Vision, Mission, Goal and program objectives offered in the College of Arts and Sciences were highly acceptable to the various stakeholders of the University.